Who Assassinated Benazir Bhutto - Shakeel Anjum, 1953- (Islamabad Dost Publications, 2010)
Benazir Bhutto, 1953-2007, former prime minister of Pakistan
Include Illustrations
Keywords: Pakistan -- Prime ministers--Assassination -- Politics and government